Young, successful, precarious? Precariousness at the entry stage of employment careers in Germany - Stefan Stuth; Kerstin Jahn (Journal of Youth Studies, 2020)
The article investigates entry-stage employment trajectories of young people in Germany, asking whether transitions into continuous employment indicate successful labour market integration. Applying a novel multidimensional approach to precariousness to individuals' employment and household trajectories, we understand entry-stage employment trajectories holistically. The balanced-panel sample is drawn from the German Socio-Economic Panel, with a focus on young men and women between 15 and 25 years of age in the first year of the sample period who had been employed at least once (n0.167em=0.167em1360).Dual-channel sequence-cluster analysis reveals considerable variation in the precariousness of young people's entry-stage employment. While almost all young men and women experience periods of precariousness, the durations vary substantially. Precarious employment or precarious living conditions frequently occur during education. Our results confirm that individuals with disrupted employment trajectories are seldom successfully integrated into the labour market and frequently experience precarious employment. In previous research, transitions into continuous employment have been understood as the hallmark of successful labour market integration. This holds true for young women but not for young men, who experienced continuous and precarious entry-stage employment. To correctly identify young men's successful labour market integration, additional information about their employment precariousness is required.
Keywords: 330; dual channel sequence cluster analysis; entry-stage employment; living conditions; precariousness; integration; volatility